Effectiveness of Travel Administration Management in Meeting the Requirements for Organizing Hajj and Umrah in Improving Congregation Services - Putri Dian Antika; Jauharotina Alfadhilah (Kawakib: Journal of Multidisciplinary Research, 2026)
The effectiveness of travel administrative management serves as the main factor in the requirements for organizing Hajj and Umrah, which has an impact on improving pilgrim services. This effectiveness is realized through three integrated service dimensions: first, administrative services; second, pilgrim guidance; and third, pilgrim direction. The study examines the organizational requirements for worship and their contribution to improving pilgrim services. The method used is library research with a descriptive qualitative approach. Data were collected from various literature sources, including books, journals, and regulations related to the organization of Hajj and Umrah in Indonesia. The effectiveness of Hajj and Umrah travel administrative management encompasses three interrelated main dimensions. Pilgrim direction as an operational-situational dimension includes the provision of health protocols, local Saudi Arabian regulations, and emergency response procedures. The effectiveness of direction depends on the accuracy of documentation of pilgrim participation and the optimization of multimodal media (print, interactive digital, and communication groups). The strategy includes a digital platform-based management system that connects administrative service data, guidance, and direction. This system enables real-time monitoring of pilgrim compliance and periodic evaluation. This study concludes that the success of travel administrative management is an absolute prerequisite for the comprehensive improvement of pilgrim services.